Influences of physical stimulations on the migration and differentiation of Schwann cells involved in peripheral nerve repair - Qingyan Sun; Xiaodan Mu; Qi Gao; Juncheng Wang; Min Hu; Huawei Liu (Cell Adhesion & Migration)
Peripheral nerve injury repair has always been a research concern of scientists. At the tissue level, axonal regeneration has become a research spotlight in peripheral nerve repair. Through transplantation of autologous nerve grafts or other emerging biomaterials functional recovery after facial nerve injury is not ideal in clinical scenarios. Great strides have been made to improve facial nerve repair at the micro-cellular level. Physical stimulation techniques can trigger Schwann cells (SCs) to migrate and differentiate into cells required for peripheral nerve repair. Classified by the sources of physical stimulations, SCs repair peripheral nerves through galvanotaxis, magnetotaxis and durotaxis. This article summarized the activation, directional migration and differentiation of SCs induced by physical stimulations, thus providing new ideas for the research of peripheral nerve repair.